Correlating Electronic Transport and 1/f Noise in MoSe2 Field-Effect Transistors - Kwon, Jiseok; Prakash, Abhijith; Das, Suprem R.; Janes, David B. (My University, 2018)
Two-Dimensional Transition Metal Dichalcogenides (2D TMDCs) such as MoS2, MoSe2, WS2, and WSe2 with van der Waal's type interlayer coupling are being widely explored as channel materials in a Schottky Barrier Field Effect Transistor (SB FET) configuration. While their excellent electrostatic control and high on/off ratios have been identified, a clear correlation between electronic transport and the low-frequency noise with different atomic-layer thickness is missing. For multilayer channels in MoS2 FETs, the effects of interlayer-coupling resistance on device conductance and mobility have been studied, but no systematic study has included interlayer effects in consideration of the intrinsic (channel) and extrinsic (total device) noise behavior. Here, we report the 1/f noise properties in MoSe2 FETs with varying channel thicknesses (3–40 atomic layers). Contributions of channel vs access/contact regions are extracted from current-voltage (transport) and 1/f noise measurements. The measured noise amplitude shows a direct crossover from channel- to contact-dominated noise as the gate voltage is increased. The results can be interpreted in terms of a Hooge relationship associated with the channel noise, a transition region, and a saturated high-gate-voltage regime whose characteristics are determined by a voltage-independent conductance and noise source associated with the metallurgical contact and the interlayer resistance. Both the channel Hooge coefficient and the channel/access noise amplitude decrease with increasing channel thickness over the range of 3–15 atomic layers, with the former remaining approximately constant and the latter increasing over a range of 20–40 atomic layers. The analysis can be extended to devices based on other TMDCs.
Citation: Kwon, J., Prakash, A., Das, S. R., & Janes, D. B. (2018). Correlating Electronic Transport and 1/f Noise in MoSe2 Field-Effect Transistors. Physical Review Applied, 10(6), 064029. https://doi.org/10.1103/PhysRevApplied.10.064029